Peranan Negara Kuat dalam Pelaksanaan Demokrasi Lokal di Indonesia: Kasus di Sumatera Barat - Asrinal Asrinaldi (Magister Ilmu Administrasi Publik, 2008)
The role of strong state to implement kical democracy is important for a state in transition. When decentralization laws UU No. 22/1999 and UU No. 25/1999 was applied, central had a lack of power to control local autonomy so that local government tends to use its power with wrong way. In this condition, the role of state is weak to manage local autonomy, as it has no effect to enhance local prosperity. Therefore, government amended UU No. 22/1999 and UU No. 25/1999 and issue of new decentralization laws UU no. 32/2004 and UU No. 33/2004. Both new decentralization laws become basic for strengthening the role of state to control local democracy in Indonesia. This paper explain teh role of strong state to employ local democracy in West Sumatra aas a subject in this study. With using structural functional approach, this paper shows that local democracy could be achieved because center had capacity to extract, distribute, regulate and reinforce the symbol of state in local society. We conclude by recommending the center for keeping the state strength to accomplish local democracy agenda.